2014
DOI: 10.1021/ma500691k
|View full text |Cite
|
Sign up to set email alerts
|

Local Flips and Chain Motion in Polyethylene Crystallites: A Comparison of Melt-Crystallized Samples, Reactor Powders, and Nanocrystals

Abstract: The crystallization and the mechanical properties of polyethylene, which is one of the most important commodity polymers, are influenced by the crystalline α-relaxation. This process originates from the diffusive chain transport through the crystallites as mediated by local 180°flips. Recent studies have stressed the relevance of the chain folding morphology on the chain diffusion, but its relation to the rate of jumps of the individual repeat units has not yet been addressed. In this study, we compare samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 63 publications
4
40
3
1
Order By: Relevance
“…Figure (a) shows that no chain diffusion was observed in the all‐atom and HB crystal model simulations, where the dashed line indicates the minimum detectable MSD, that is, the amount of displacement caused by a single chain slip during the simulation time span. This observation is consistent with the range of diffusion coefficients reported from nuclear magnetic resonance experiments performed on polyethylene nanocrystals, reactor powders, and melt‐crystallized samples, which range from 10 −16 to 10 −15 cm 2 s −1 . Assuming that the intracrystalline chain diffusion rate was accurately reproduced by the molecular models, a simulation time on the order of 100 μs would be needed to observe a single chain slip at room temperature.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Figure (a) shows that no chain diffusion was observed in the all‐atom and HB crystal model simulations, where the dashed line indicates the minimum detectable MSD, that is, the amount of displacement caused by a single chain slip during the simulation time span. This observation is consistent with the range of diffusion coefficients reported from nuclear magnetic resonance experiments performed on polyethylene nanocrystals, reactor powders, and melt‐crystallized samples, which range from 10 −16 to 10 −15 cm 2 s −1 . Assuming that the intracrystalline chain diffusion rate was accurately reproduced by the molecular models, a simulation time on the order of 100 μs would be needed to observe a single chain slip at room temperature.…”
Section: Resultssupporting
confidence: 84%
“…With a 10 nm domain length along the c axis, the extrapolated diffusion rate from the HB model is D = 5 × 10 −11 cm 2 s −1 . This is larger than the diffusion rate, D = 10 −15 cm 2 s −1 , measured by Bärenwald et al in polyethylene nanocrystals of comparable thickness; however, our simulations do not account for the constraining effects that the outer 1 nm thick amorphous layers made up of tight chain folds have on the chain mobility.…”
Section: Resultscontrasting
confidence: 61%
“…Erstmals war es möglich, die Menge an immobilisiertem Material in einem anwendungsrelevanten Elastomer quantitativ zu erfassen und dessen Temperatur‐ und Füllgradabhängigkeit direkt mit dem frequenzabhängigen Elastizitätsmodul zu korrelieren. Einfache, aber leistungsfähige Protonen‐NMR‐Methoden zeigten zudem auf molekularer Ebene, wie relevant die Morphologie von semikristallinem Polyethylen (PE) für die mechanisch aktive Kettenbeweglichkeit in den Kristalliten ist 1_70. Dies wurde primär durch Vergleich konventioneller PEs mit einzigartigen PE‐Nanokristallen aus der Gruppe um Mecking ermöglicht und letztlich in einer Korrektur1_71 zur vorab erschienenen Originalpublikation1_70 herausgestellt.…”
Section: Magnetische Methoden In Der Polymerforschungunclassified
“…It was found that a short echo time (t CPMG 25 ms) and short MSE duration (t initial 25 ms) drastically improved the fit quality as the fast relaxing amorphous component could only be modeled accurately when a sufficient number of echoes was recorded during the initial 200 ms? For the polyethylenes the MSE intensity decreased significantly at the respective crystallization temperatures, potentially due to 180 chain flips acting on the time scale of the MSE refocusing blocks [75,76]. The indirect method, based only on the CPMG part, offered a more robust way to obtain crystallinities as it is independent of the MSE efficiency.…”
Section: Monitoring Polymer Crystallization and Crystallization Kineticsmentioning
confidence: 99%